Influence of vertical grouting steel-tube connection mode on anti-sliding performance - Wei, Shaowei; Zhang, Xinshang; Qin, Chuan; Wei, Peiyong; Qin, Shangyou; Liu, Li; Chen, Qian; Yin, Chuan (Frontiers in Earth Science, 2022)
Steel-tube grouting technology has been widely applied in the slope control engineering. While the anti-sliding performances of different connection modes of grouted steel tubes still needs further investigation. In this paper, a large-scale model test was used to study the influence of three types of pile connections, namely a whole pile without connection, with a reinforcement welded connection, and with a casing connection, on the anti-sliding performance of multi-stage grouted steel-tube pile. The results showed that the slope could be reinforced by all multi-stage grouted steel-tube pile structures controlled by different pile connection modes, and the composite anti-sliding body of the “root-shape” cement column could be formed around the pile, which effectively improved the perimeter of the pile and enhanced the anti-sliding performance of steel-tube pile structure. The steel-tube piles with different pile connection modes all suffered from bending failure near the sliding surface. The horizontal anti-sliding force of the welded steel tube 6 m in length was 1.4 t per root, which was higher than that of the whole pile. The horizontal anti-sliding force of steel casing connected steel-tube with 6 m in length was 8.8 t per root, which was higher than that of the whole pile. The casing connected steel tube had stronger anti-sliding ability due to the increased diameter of the steel tube near the sliding surface. Therefore, it is recommended that the casing connection mode be used in the connection design of steel pipes, and the reinforcement of a pile body near the sliding surface should be strengthened to improve the flexural failure capacity.